2022
DOI: 10.2147/ijn.s365974
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated SLN as a Promising Approach for Lymphatic Delivery of Gefitinib to Lung Cancer

Abstract: Purpose The present study aimed to develop gefitinib-loaded solid lipid nanoparticles (GEF-SLN), and GEF-loaded PEGylated SLN (GEF-P-SLN) for targeting metastatic lung cancer through the lymphatic system. Methods The prepared SLNs were characterized in terms of physicochemical properties, entrapment efficiency, and in-vitro release. Furthermore, ex-vivo permeability was investigated using the rabbit intestine. Cytotoxicity and apoptotic effects were studied against A549… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
(105 reference statements)
3
23
0
Order By: Relevance
“…The presence of GEF in solid lipids instead of liquid oil resulted in the disruption of SA crystallization. In a similar context, Sherif et al found that the incorporation of a drug within a solid lipid resulted in a disruption in SA crystallinity [ 2 ]. Regarding ZP, the incorporation of GEF resulted in increased ZP value in the case of GEF-NLC (LCT) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of GEF in solid lipids instead of liquid oil resulted in the disruption of SA crystallization. In a similar context, Sherif et al found that the incorporation of a drug within a solid lipid resulted in a disruption in SA crystallinity [ 2 ]. Regarding ZP, the incorporation of GEF resulted in increased ZP value in the case of GEF-NLC (LCT) .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in our previous work, GEF-SLN formulation contained a solid lipid only where GEF was expected to be homogenously distributed within SA ( Figure 9 ). An in vitro release study revealed that about 74% of the drug was released within 24 h [ 2 ]. Herein, about 50% GEF was released within 24 h from GEF-NLC (LCFA) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations